The Significance and Place of Applied Art in the Development of Aesthetic Taste of People (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the history of the development of folk art, its role in people's lives and its influence on the formation of the aesthetic worldview, the comparison of folk art with the art of the peoples of the world, the problem of the present time and its versatility and complexity are important. information is given that it is considered as a factor.